Potential alkali reactivity of aggregates for concrete in Uruguay. Correlation between mortar bar test and concrete prism (accelerated and traditional test) - Vila, Patricia; Bonjour, Hugo; Díaz, Leandro; Pereyra, María Noel (Revista ALCONPAT, 2022)
The correlation between the international criteria to define the reactivity degree in the mortar bar expansion tests and the expansion in concrete prism tests (accelerated and traditional methodology) was analyzed. The three test methodologies were applied experimentally to 19 aggregates samples used for concrete in Uruguay. There were aggregates of different reactivity degree, but no consensus was found in the interpretation by the different techniques. The results are only for the lithologies evaluated and provided background for a relatively new assay methodology. No correlation was observed between the expansion of the mortar bar and in the concrete prism-traditional methodology, but an adequate correlation was observed between both concrete methodologies (accelerated and traditional).